Dinitrogen activation by silicon and phosphorus doped aluminum clusters - Das, Susanta; Pal, Sourav; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2014)
N-2 reduction is crucial for life, and very few catalysts are currently available to carry out this process at ambient temperature and pressure. In the present work, density functional theory based calculations reveal doped aluminum clusters to be highly reactive toward molecular nitrogen and hence are prospective materials for its activation at low temperatures. Calculations on silicon and phosphorus doped aluminum clusters with 5-8 atoms demonstrate an enhanced N-2 activation with respect to their pristine ground state and high energy counterparts. This increased efficiency of N-2 activation by doped ground state Al clusters is corroborated by an increment of the N N bond length, a red shift in N N bond stretching frequency, and adsorption energy (E-ad). Ab initio molecular-dynamics simulations demonstrate consequential efficiency of doped clusters toward dinitrogen activation at finite temperature. The ability of doped clusters toward activation of molecular nitrogen is site and shape sensitive. In short, this theoretical study highlights the critical role of doping foreign impurities for future endeavors in the design of cost-effective and efficient catalysts for N-2 activation at ambient temperatures. This observation may spur further studies in the field of aluminum nanocatalysis by doping silicon and phosphorus atom in aluminum clusters.